Implikasi Undang – Undang Nomor 1 Tahun 2022 Terhadap Keberadaan Pajak Daerah Sebagai Sumber PAD Kabupaten/Kota di Provinsi Sumatera Barat - Fithrina, Hendria; Gusminarti, Gusminarti; Darnis, Darnis; Kurniawan, Fajri (Faculty of Law, Andalas University, 2024)
The implications of Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments, are improvements to Law Number 28 of 2009 concerning Regional Taxes and Regional Levies. In Law Number 1 of 2022, there are changes to the components of regional tax types in districts/cities in Indonesia, one of the aims of which is to increase the regional PAD. The seriousness of the Regency/City Government in implementing the regulations in this Law will be very beneficial for regional income from the tax sector. For this reason, research was carried out on the following problems: First, what is the regional government's view of the implications of Law Number 1 of 2022 in West Sumatra? Second, how is the implementation of Law Number 1 of 2022 regarding the existence of Regional Taxes in West Sumatra? Third, what are the obstacles faced and the solutions implemented in implementing Law Number 1 of 2022 in West Sumatra? To answer the research focus, this research uses empirical juridical research methods with research specifications from the West Sumatra Bapenda, Padang City Government Bapenda and West Pasaman Regency Bapenda, and is analyzed through literature review and data analysis methods using qualitative-juridical. A number of stages must be carried out by the government, such as completing the drafting of implementing Regional Regulations as intended in the a quo statutory regulations, conducting regional potential studies with consultants to determine the potential for regional tax revenue in the Regency/City, then carrying out socialization to the community as mandatory taxes, as well as technical guidance to tax collector employees within the Regional Government Organization (OPD) in order to maximize the potential of regional wealth in Regencies/Cities in West